ПРИНЦИПЫ ГУМАНИЗАЦИИ ОБРАЗОВАНИЯ И ПРОЦЕСС ОБУЧЕНИЯ. - Гасанова, Гульшен Октай кызы (Journal of Educational Sciences, 2016)
Автор мақаласында білім жэəне оқыту үдерісіндегі гуманизм принциптеріне тоқталады. Acceptance in attention of a principle of a humanization of formation in the course of training is considered expedient and useful. As it is known, in high school life the big possibilities for realization of a principle of a humanization of education are had.